Case series of Ectopia Lentis associated with Marfan's syndrome - Sagarika Laad; Harpal Singh; Satendra Singh; Parag Ramnani; Shashank Gupta; Ritu Gupta (Delhi Journal of Ophthalmology)
Purpose: To report 4 cases of Marfan's syndrome with ectopia lentis. Methods: Case 1- Fifty year old woman presented with sudden painless diminution of vision both eye since 1 day with history of blunt trauma by wood-log. Vision was counting finger 3 feet in both eyes, small pupil with sluggish reactions and posteriorly dislocated lens. B-scan showed posterior dislocation of lens in both eyes with retinal detachment in right eye. Case 2- Two sisters aged 15 and 12 year also presented with superotemporal subluxation of lens. Best corrected vision was 6/12 both eye in younger one and 6/9 in right and 6/12 in left eye of elder one. Case 3- A 22 year old male reported with painless diminution of vision since childhood. Vision was 1/60 in right and 6/60 in left eye. Anterior segment shows lens in anterior chamber in right eye and superonasal subluxation of lens in left eye. All patients presented with typical features of Marfan's syndrome like tall-statured with long, thin extremities; arachnodactly, prognathis and a high arched palate. Results: Case 1 improved with +10 D lens in left eye and no improvement in right as there was Retinal detachment present. She was referred to vitreoretinal surgeon. Case 2 are under observation and managed conservatively. Case3 is also referred to vitreoretinal surgeon. Conclusion-Ectopia lentis is reported as most common feature in Marfan's syndrome. Though posterior dislocation is rarely reported. There should be multifaceted approach to manage such cases and prevent sight-threatening complication.